2021
DOI: 10.3390/su13148072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate Change on Cultivation Patterns and Climate Suitability of Spring Maize in Inner Mongolia

Abstract: Climate change has caused significant alterations in crop cultivation patterns and has affected crop suitability as well as its production. In this study, we investigated the changes in cultivation patterns and climate suitability of spring maize in Inner Mongolia from 1959 to 2018. We used the daily meteorological data from 50 weather stations and growth period data of spring maize from nine agrometeorological stations. In addition, the quantitative and interdecadal relationship between climate suitability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…For example, Ojara et al (2021) projected that area highly suitable for maize in Eastern Africa will decrease by more than 50% under the RCP8.5 scenario by the mid-century but if extreme indices were included, the decreases could be worse. Many studies have projected maize suitability changes without incorporating extreme variables (Holzkämper et al, 2013;Adisa et al, 2018;Lopez-Blanco et al, 2018;Kogo et al, 2019;Mumo et al, 2021;Yang et al, 2021), and the reported changes may need to be revisited in light of our findings.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Ojara et al (2021) projected that area highly suitable for maize in Eastern Africa will decrease by more than 50% under the RCP8.5 scenario by the mid-century but if extreme indices were included, the decreases could be worse. Many studies have projected maize suitability changes without incorporating extreme variables (Holzkämper et al, 2013;Adisa et al, 2018;Lopez-Blanco et al, 2018;Kogo et al, 2019;Mumo et al, 2021;Yang et al, 2021), and the reported changes may need to be revisited in light of our findings.…”
Section: Discussionmentioning
confidence: 91%
“…The primary factors influencing sweet sorghum growth include temperature, sunshine duration, and precipitation. Therefore, this study assessed the suitability of temperature, sunshine, and water for sweet sorghum at various growth stages [61].…”
Section: Climate Suitability For Sweet Sorghummentioning
confidence: 99%
“…Zhao et al [28] constructed a climatic suitability model to analyze the climatic suitability and changes in potato-planting zoning in North China. However, most of the previous studies focused on food and fruit crops [29][30][31][32][33][34]. Therefore, a comprehensive suitability model for sesame should be built to evaluate the climatic suitability of sesame in China by considering the temperature, precipitation, and sunshine suitability.…”
Section: Introductionmentioning
confidence: 99%